Estudio de prefactibilidad para la instalación de una planta procesadora de snacks de zanahoria deshidratada - Sánchez Jugo, Juan Ignacio (2020)
In order to develop high standard products and considering a market scenario that includes a bigger concern about healthy food and the low offering of healthy snacks, the following project takes place; searching to determine the technical, economic and social viability of the implementation of a production plant of dehydrated carrots snacks by industrial ovens, which machines are available in the market and they have low technical complexity.